How the IBOR reform affects interest rate swaps - Josua Goebel; Thomas Heidorn; Zizhen Huang (Frankfurt School of Finance & Management, 2022)
This paper examines how the IBOR Reform affects interest rate swaps (IRS), focusing on Euro and US Dollar. The effects are derived by (1) studying publications from the standard setting bodies behind the reforms and (2) by analyzing swap conventions and clearing eligibility criteria at LCH, CME, and Eurex. The paper finds a limited impact on Euro IRS, as it has retained its credit-risky and forward-looking benchmark rate in the (hybrid) EURIBOR. The largest adjustment has been the shift from EONIA to exteuroSTR OIS discounting. USD IRS will move from USD LIBOR to the overnight rate SOFR. Consequently, interest rates are calculated by compounding the daily SOFR rates over the interest period. As the rate is no longer forward-looking, the floating rate is set at the end of the interest period ("fixed in arrears"). SOFR does not contain a term premium and is nearly risk free unlike USD LIBOR. One direct result is a lower swap rate. Moreover, banks no longer have an interest rate that captures their funding costs. Lastly, EURUSD cross currency swaps now mostly exchange exteuroSTR for SOFR instead of EURIBOR for USD LIBOR, which has increased the cross-currency basis.
Keywords: G12; G23; G28; 330; IBOR Reform; LIBOR; SOFR; exteuroSTR; EURIBOR; RFRs; Overnight rate; OIS; Compounding in arrears; Interest rate swaps; Cross currency swaps